Historical perspectives : from the hasmoneans to bar kokhba in light of the dead sea scrolls. (Brill, 2001)
The papers in this volume cover topics such as: the historical references in the Dead Sea Scrolls, comparative studies between the Scrolls and Josephus, issues of Jewish nationalism, Jewish law, and reports on DNA preserved in leather used for the scrolls.